Levelling up and the privileging of sub-national governance in England in the inter-Brexit space - Alex Nurse; Olivier Sykes (ZFW - Advances in Economic Geography, 2023)
Although the UK's exit from the European Union - 'Brexit' - has overwhelmingly dominated the national political discourse since 2016 to the expense of nearly every other domestic issue, the policy agenda in the wake of this process is beginning to emerge. This paper examines this agenda, ostensibly supporting a programme of 'levelling up' which responds to the perceived root-causes of Brexit. In doing so, we consider the funding streams proposed by the UK Government - namely the Towns Fund, Shared Prosperity Fund and Levelling Up Funds - and examine the extent to which the rhetoric aligns with the reality of their allocation. In doing so, we also consider how, if at all, these schemes correspond to the European Structural Investment Funds (ESIF) they are intended to replace. This paper examines this period of change to consider how the Brexit process is mirroring, and indeed entrenching, these processes of uneven development. We find that the early indications suggest that the UK government is proceeding with funding allocations in a way which can overlook places which meet the technical funding criteria, and therefore indicates political favouring is at play.
Keywords: 330; Brexit; levelling up; United Kingdom